Electrochemical carbon dioxide reduction to isopropanol using novel carbonized copper metal organic framework derived electrodes. Issue 39 (July 2020) - Rayer, Aravind V.; Reid, Elliot; Kataria, Atish; Luz, Ignacio; Thompson, Samuel J.; Lail, Marty; Zhou, James; Soukri, Mustapha
Graphical abstract: Highlights: Electrochemical conversion of CO2 into isopropanol using Cu-MOFs. Techno-Economic assessment for electrochemical isopropanol production. Carbonized Cu-MOFs yielded better current density for isopropanol. Carbonized Cu-MOFs produced improved selectivity for isopropanol. An economically feasible electroctrochemical reduction of CO2 process. Abstract: It is well known in sustainable energy research that metallic copper functions as an electrocatalyst for the reduction of CO2 to multicarbon products such as alcohols and hydrocarbons. However, it remains a great challenge to develop a cost-effective, selective, and stable catalyst/electrode material for this reaction. This work furthers previous studies concerning the potential of carbonized copper MOF-derived electrocatalysts as catalyst materials for the electrochemical reduction of CO2 . Two commercial copper-decorated metal organic frameworks (MOFs), HKUST-1 and PCN-62, pyrolyzed at variable temperatures, 400−800 °C, were coated on both metallic nickel and copper supports as inks. The electrocatalysts' potential to reduce CO2 was gauged using an electrochemical cell with both GC-TCD and GC-FID analyses. Many of the previously reported products of this reaction were formed, however, most notably, GC-FID analysis confirmed the formation of isopropanol, a product not previously reported to the best of our knowledge. It was observed that MOF-derived coatings can produce electrodes with both better current density and selectivity towards isopropanol compared to that of uncoated copper electrodes. Amongst all the carbon products observed, the best performing electrocatalyst demonstrated isopropanol faradaic efficiency (FE) of over 72 %. Preliminary techno-economic analysis was conducted to identify target cell operating voltage in order to make the proposed electrochemical CO2 reduction process economically feasible. The desired cell operating voltage is less than 1.9 V, preferably less than 1.6 V. Future work will focus on electrochemical cell design and electrocatalyst morphology to further improve isopropanol selectivity and minimize hydrogen FE.